Campaign trends and election law - H.W. Wilson Company (Amenia, New York : Grey House Publishing, 2016)
"In the run-up to the 2016 national election, many issues involving election law have come to the fore. This volume will explore such timely topics as campaign finance and the corporate funding of elections in the aftermath of Citizens United vs. Federal Election Commission (2010), which opened the door to unlimited corporate and private funding of candidates in federal elections. The volume will also investigate the effects of SCOTUS's ruling to roll back various aspects of the Voting Rights Act of 1965, allowing states to make their own election laws--including instituting voter ID laws and cancelling early voter registration--without federal oversight. Other important issues under discussion include the rise of one-party domination of state government and the subsequent, unprecedented gerrymandering of districts; the use of initiatives and referendums to mobilize political bases; and the changing uses of social media in campaigns. Articles will also examine the rise of political dissidents both inside and outside the two major parties"--Publisher description.
1. Election laws, redistricting, campaign financing, corporate fundraising. Cash and constituency: campaign financing and partisan electoral manipulation -- Drawing the line: how redistricting turned America from blue to red / Elizabeth Kolbert -- What is political "dark money" -- and is it bad? / Michael Beckel -- How "ghost corporations" are funding the 2016 election / Matea Gold and Anu Narayanswamy -- Why redistricting threatens democracy / John Nichols -- Voting rights become a proxy war in the 2016 presidential election / Frank Askin -- How Citizens United has changed politics in 5 years / Gabrielle Levy -- The many sins of "Citizens United" / Senator Sheldon Whitehouse -- The first postmodern political machine / Walter Russell Mead -- 2. Election laws, redistricting, campaign financing, corporate fundraising. Political outsiders: class, race, and gender in the 2016 election -- The woman card: how feminism and antifeminism created Hillary Clinton and Donald Trump / Jill Lepore -- Working-class heroes: the 2016 election shows that, when talking about class, Americans and their candidates are both out of practice / Jelani Cobb -- Outsiders' chance / The Economist -- Class, Trump, and the election / Victor David Hanson -- Race, class, and the 2016 election / Keeanga-Yamahtta Taylor -- The great Republican revolt / David Frum -- Trump's America / Charles Murray -- Identity heft: why the politics of race and gender are dominating the 2016 election / Jeet Heer -- The populists / George Packer -- 3. Campaign issues: immigration, trade, the economy. Identity and economics: immigration and globalization in the 2016 race -- The truth about trade: what critics get wrong about the global economy / Douglas A. Irwin -- Immigration and the 2016 election / Victor Agbafe -- Even conservatives say Trump's immigration plan is dystopian / Issie Lapowsky -- Supreme Court's split elevates immigration as election issue / Mike Dorning -- Simmering for decades, anger about trade boils over in '16 election / Binyamin Appelbaum -- Why the conditions were perfect for Bernie's socialist crusade / Robert Kuttner -- Election 2016 is propelled by the American economy's failed promises / Jon Hilsenrath and Bob Davis -- 4. Campaign messaging: language, social media, video. News and information in the 2016 campaign -- The rhetorical brilliance of Trump the demagogue / Jennifer Mercieca -- Who's influencing election 2016? / William Powers -- Here's how social media will impact the 2016 presidential election / Rohan Ayyar -- 2016 presidential election circus: is social media the cause? / Marissa Lang -- Digital video plays critical role in 2016 election / Philip Rosenstein -- Foul-mouthed and proud of it on the '16 campaign trail / Matt Flegenheimer and Maggie Haberman -- What Google and Twitter can tell us about 2016 / Daniel White -- Facebook to provide "political bias" training for employees / Rob Bluey -- The polls are all wrong: a startup called Civis is our best hope to fix them / Garrett M. Graff.
Includes bibliographical references (pages 189-193) and index.
Keywords: Political campaigns -- United States; Election law -- United States; Elections -- United States; Campaign funds -- United States; Social media -- Political aspects -- United States; Voting -- United States; 2000-2099